Development of a low pressure chromatographic flow system for monitoring the biodegradation of ofloxacin and ciprofloxacin. Issue 27 (24th June 2016) - Santos, Inês C.; Mesquita, Raquel B. R.; Amorim, Catarina L.; Castro, Paula M. L.; Rangel, António O. S. S.
Abstract : In this work, we propose a simple low pressure chromatography method with a high throughput for monitoring the biodegradation of fluoroquinolones. Abstract : In this work, we propose a simple low pressure chromatography method with a high throughput for monitoring the biodegradation of fluoroquinolones. Fluoroquinolones are a class of antibiotics that have been accumulating in the environment as a consequence of their release from different sources, namely hospital waste. It has been found that wastewater treatment plants are not able to completely remove this type of micro-pollutants and so, alternative solutions are necessary. Some biodegradation studies have been done but the HPLC-based methodologies used to monitor the degradation process usually require high cost instrumentation such as analytical columns and detectors. For this reason, a 1 cm monolithic column was coupled to a flow injection system and used for the simultaneous quantification of ofloxacin and ciprofloxacin with UV detection at 295 and 275 nm, respectively. LODs of 0.5 and 0.29 mg L −1 for ofloxacin and ciprofloxacin were obtained, respectively, with repeatability within the range of 2–10%. The developed method was successfully applied to monitor the biodegradation of ofloxacin and ciprofloxacin by the strain Labrys portucalensis F11. The results proved that the low pressure chromatography method is a simpler, cheaper, and faster alternative to monitor biodegradation studies.